Answer:
y = -7, y = -3
Step-by-step explanation:
(y - 3)² = 2y² + 4y + 30
expand:
y² - 6y + 9 = 2y² + 4y + 30
subtract 30 from both sides
y² - 6y + 9 - 30= 2y² + 4y + 30 - 30
simplify:
y² - 6y - 21 = 2y² + 4y
subtract 4y from both sides
y² - 6y - 21 -4y = 2y² + 4y - 4y
simplify:
y² - 10y - 21 = 2y²
subtract 2y² from both sides
y² - 10y - 21 - 2y² = 2y² - 2y²
simplify:
-y² - 10y - 21 = 0
solve y by quadratic equation
- (-10) ± √ (-10² - 4(-1)(21)
y = --------------------------------------
2(-1)
y = -7, y = -3